Stroboscopic lighting with intensity synchronized to rotation velocity alleviates motion sickness gastrointestinal symptoms and motor disorders in rats - Mao, Yuqi; Pan, Leilei; Li, Wenping; Xiao, Shuifeng; Qi, Ruirui; Zhao, Long; Wang, Junqin; Cai, Yiling (Frontiers in Integrative Neuroscience, 2022)
Motion sickness (MS) is caused by mismatch between conflicted motion perception produced by motion challenges and expected “internal model” of integrated motion sensory pattern formed under normal condition in the brain. Stroboscopic light could reduce MS nausea symptom via increasing fixation ability for gaze stabilization to reduce visuo-vestibular confliction triggered by distorted vision during locomotion. This study tried to clarify whether MS induced by passive motion could be alleviated by stroboscopic light with emitting rate and intensity synchronized to acceleration–deceleration phase of motion. We observed synchronized and unsynchronized stroboscopic light (SSL: 6 cycle/min; uSSL: 2, 4, and 8 cycle/min) on MS-related gastrointestinal symptoms (conditioned gaping and defecation responses), motor disorders (hypoactivity and balance disturbance), and central Fos protein expression in rats receiving Ferris wheel-like rotation (6 cycle/min). The effects of color temperature and peak light intensity were also examined. We found that SSL (6 cycle/min) significantly reduced rotation-induced conditioned gaping and defecation responses and alleviated rotation-induced decline in spontaneous locomotion activity and disruption in balance beam performance. The efficacy of SSL against MS behavioral responses was affected by peak light intensity but not color temperature. The uSSL (4 and 8 cycle/min) only released defecation but less efficiently than SSL, while uSSL (2 cycle/min) showed no beneficial effect in MS animals. SSL but not uSSL inhibited Fos protein expression in the caudal vestibular nucleus, the nucleus of solitary tract, the parabrachial nucleus, the central nucleus of amygdala, and the paraventricular nucleus of hypothalamus, while uSSL (4 and 8 cycle/min) only decreased Fos expression in the paraventricular nucleus of hypothalamus. These results suggested that stroboscopic light synchronized to motion pattern might alleviate MS gastrointestinal symptoms and motor disorders and inhibit vestibular-autonomic pathways. Our study supports the utilization of motion-synchronous stroboscopic light as a potential countermeasure against MS under abnormal motion condition in future.